Fortificação do leite fluido na prevenção e tratamento da anemia carencial ferropriva em crianças menores de 4 anos - Torres, Marco A. A.; Lobo, Neil F.; Sato, Kazue; Queiroz, Suzana de Souza [UNESP] (FapUNIFESP (SciELO), 1996)
The effectiveness of the use of chelate aminoacid iron fortified fluid milk in the treatment of iron deficiency in children under four years of age was studied. The 269 children included in this trial received 1 liter/day of fluid milk fortified with 3 mg of chelate aminoacid iron and were evaluated at six monthly intervals. At the beginning of the study 62.3% of the children presented anemia. After 6 months, this percentage had decreased to 41.8% and at the end of one year to 26.4%. The greatest decreases occurred in the groups comprising the subjects who were of 12 to 23 months of age and those under one year of age. Among the children who presented initial hemoglobin levels under 9.5 g/ dl, 59.3% were free of anemia after one year of follow-up. Of those presenting initial hemoglobin levels between 9.5 and 10.9 g/dl, 66.7% recovered from their anemia. There was also greater hematological improvement in the children that ingested over 750 ml/day of fortified milk in those families that did not share the supply of supplement among their other members and in those families that had only one child under five years of age. These findings led to the conclusion that the fortification of fluid milk is a viable and effective method for the treatment of iron deficiency in pre-school children.
Fortification of fluid milk for the prevention and treatment of iron defficiency anemia in children under 4 years of age
Keywords: Anemia, iron-deficiency, prevention and control; Food, fortified, utilization; Supplemantaty feeding; hemoglobin; iron chelating agent; analysis of variance; animal; blood; chi square distribution; clinical trial; comparative study; diet supplementation; follow up; human; infant; iron deficiency anemia; milk; preschool child; prevalence; Analysis of Variance; Anemia, Iron-Deficiency; Animals; Chi-Square Distribution; Child, Preschool; Follow-Up Studies; Food, Fortified; Hemoglobins; Humans; Infant; Iron Chelating Agents; Milk; Prevalence